Bioresource collection of cell lines and primary tumors of the National Medical Research Center of Oncology of the Ministry of Health of Russia - S. V. Timofeeva; S. Yu. Filippova; A. O. Sitkovskaya; N. V. Gnennaya; I. V. Mezhevova; T. V. Shamova; L. M. Vashchenko; V. E. Kolesnikov; I. A. Novikova; O. I. Kit (Кардиоваскулярная терапия и профилактика)
The Biobank of the National Medical Research Center of Oncology is a multi-layered infrastructure with large collections of biological samples, complemented by extensive and well-annotated clinical and pathological patient data, including medical images, pathological histology, and molecular analysis of biosamples. To date, the biobank of the National Medical Research Center of Oncology contains collections of primary and immortalized cancer cell lines of human origin. The collection of primary cell lines was formed from samples of postoperative material taken during the removal of tumors of various localizations (breast cancer, prostate cancer, lung cancer). All cell lines underwent internal quality control for contaminants (exogenous viruses, mycoplasmas and bacterial L-forms), viability and were cultivated without antibiotics. On the basis of the collected samples, a significant number of projects in the field of biomedicine were carried out, the results of which are described in this article.